(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2017)
Moral bioenhancement is strictly related to the notion of Human Enhancement. In general terms, the proposal fosters interventions by means of pharmaceutical and non-pharmaceutical tools into the human mind to make individuals become morally better. In order to understand the ethical-legal implications of this proposal, the paper will try to answer, amongst others, the following questions: Is identification of the target group of the proposal easy today? Is the traditional distinction between healthy individuals and patients so clear? What may be the implications of moral bioehancement for the rights to self-determination and construction of one’s personality?